Real-Time Emissions Modeling with Environmental Protection Agency MOVES: Framework Development and Preliminary Investigation. Issue 1 (January 2015) - Park, Sangjun; Ahn, Kyoungho; Rakha, Hesham A.; Lee, Chungwon
The objective of this study was to develop a framework for real-time emissions modeling to improve ecofriendly intelligent transportation system (ITS) applications. The proposed framework can be utilized for real-time ITS applications, such as ecorouting, and applications for the environment with a real-time information synthesis program. To develop a more efficient framework, a new interface with the motor vehicle emission simulator (MOVES) model was developed to enhance computational performance. In addition, a methodology that used a probe vehicle equipped with onboard equipment was suggested for collecting operating mode distribution through the network to generate input for the MOVES model. Through virtual implementation with a simulation environment developed with the Python scripting language, this study demonstrated that the proposed framework generally worked as designed. The study also investigated the effects of probe vehicle sampling size on estimation accuracy.